The effect of curcumin and its nanoformulation on adjuvant-induced arthritis in rats - Zheng ZL; Sun YH; Liu ZL; Zhang MQ; Li CQ; Cai H (Dove Medical Press, 2015)
Zhaoling Zheng,1,* YanHua Sun,2,* Ziliang Liu,1 Mingqin Zhang,1 Chunqing Li,1 Hui Cai3 1Department of Traditional Chinese Medicine, Dongying People’s Hospital, Dongying, 2Shandong Provincial Key Laboratory of Microparticles Drug Delivery Technology, Jinan, 3Department of Integrated Traditional Chinese Medicine and Western Medicine, Nanjing Jinling Hospital, Nanjing, People’s Republic of China *These authors contributed equally to this work Background: Rheumatoid arthritis (RA), induced by the prolonged inappropriate inflammatory responses, is one of the most prevalent of all chronic inflammatory joint diseases. Curcumin (CM), a yellow hydrophobic polyphenol derived from the herb turmeric, has various pharmacological activities against many chronic diseases and acts by inhibiting cell proliferation and metastasis and downregulating various factors, including nuclear factor kappa B, interleukin-1β and TNF-α. Given the pathogenesis of RA, we hypothesized that the drug also has antiarthritic effects. The aims of the present study included the following: 1) examining the therapeutic effect of CM administered via intravenous (iv) injection on RA and 2) formulating the drug into oil–water nanoemulsions (Ns) to overcome the low oral bioavailability of CM and achieve oral delivery of the drug.Methods: The effect of CM administered through iv injection on adjuvant-induced arthritis in rats was studied in terms of paw swelling, weight indices of the thymus and spleen, and pathological changes in nuclear factor kappa B expression and inflammatory cytokines. Methotrexate was used as a positive control. The CM-Ns were prepared using a high-pressure homogenizing method and characterized with respect to the particle size and morphology. The stability of the CM-Ns in simulated gastrointestinal (GI) fluids and in vitro release were also investigated. A pharmacokinetic study of the CM-Ns and suspensions in which the plasma levels were determined using an high performance liquid chromatography method and the pharmacokinetic parameters were calculated based on a statistical moment theory was also performed in rats.Results: CM administered via iv injection had a therapeutic effect on RA similar to methotrexate. CM-Ns with a diameter of approximately 150 nm were successfully prepared, and the drug was well encapsulated into the Ns without degradation in simulated GI conditions. The area under the curve (AUC) and Cmax for the CM-Ns were more than threefold greater than those for the suspensions; moreover, similar decreases in the levels of TNF-α and interleukin-1β in both synovial fluid and blood serum were obtained from oral administration of CM-Ns and iv injection.Conclusion: CM was an effective antiarthritic agent, and the present N formulation appeared to be a promising system that allowed RA therapy with CM to be converted from iv to oral administration. Keywords: curcumin, nanoemulsions, inflammatory cytokines, adjuvant-induced arthritis, drug release, oral bioavailability